Efektivitas Kampanye Humas dalam Promosi Praktek Lingkungan Berkelanjutan di Organisasi - Sitti Nurrachmah (Syntax Corporation Indonesia, 2024)
Environmental sustainability is becoming an increasingly urgent global issue. Organizations need to take an active role in promoting sustainable environmental practices to reduce negative impacts on the environment. Public relations campaigns are one strategy that can be used to increase awareness and encourage stakeholder participation in environmental conservation efforts. This research aims to analyze the effectiveness of public relations campaigns in promoting sustainable environmental practices in organizations. This study uses a qualitative method. Data collection was carried out through interviews, observation and document analysis. The collected data was analyzed in three stages: data reduction, data presentation, and drawing conclusions. The collected data was analyzed in three stages: data reduction, data presentation, and drawing conclusions. The research results show that public relations campaigns can be an effective tool for promoting sustainable environmental practices in organizations. However, to achieve maximum effectiveness, public relations campaigns must be designed and implemented well by considering the factors of employee involvement, message consistency, management support, measurement and evaluation.